Generation and implementation of reporter BHK-21 cells for live imaging of flavivirus infection - Arias Arias, Jorge Luis (2021)
The genus Flavivirus within the family Flaviviridae includes many viral species of medical importance, such as yellow fever virus (YFV), Zika virus (ZIKV), and dengue virus (DENV), among others. Presently, the identification of flavivirus-infected cells is based on either the immunolabeling of viral proteins, the application of recombinant reporter replicons and viral genomes, or the use of cellbased molecular reporters of the flaviviral protease NS2B-NS3 activity. Among the latter, our flavivirusactivatable GFP and mNeptune reporters contain a quenching peptide (QP) joined to the fluorescent protein by a linker consisting of a cleavage site for the flavivirus NS2B-NS3 proteases (AAQRRGRIG). When the viral protease cleaves the linker, the quenching peptide is removed, and the fluorescent protein adopts a conformation promoting fluorescence. Here we provide a detailed protocol for the generation, selection and implementation of stable BHK-21 cells expressing our flavivirus geneticallyencoded molecular reporters, suitable to monitor the viral infection by live-cell imaging. We also describe the image analysis procedures and provide the required software pipelines. Our reporter cells allow the implementation of single-cell infection kinetics as well as plaque assays for both reference and native strains of flaviviruses by live-cell imaging.